CD80 and IL-2 signals cooperate in the regression of tumors transplanted in congenitally athymic mice - Sobota, V; Indrová, M; Rössner, P; Bubeník, J; Jandlová, T (Oncology reports, 1999)
Interleukin-2 and CD80 transfectants of a methylcholanthrene-induced murine sarcoma Mc12 (Mc12-IL-2 and Mc12-CD80 cells) with similar tumorigenicity in euthymic mice were utilized for experiments designed to investigate a co-stimulatory role of the CD80 molecule in allogeneic, congenitally athymic (nu/nu) mice. The CD80-transfected cells were as tumorigenic in nu/nu mice as the parental Mc12 sarcoma. The IL-2-transfected cells grew only transiently and regressed in all nu/nu recipients during four weeks after challenge with doses up to 5x10(7) cells. The 1:1 mixture of parental Mc12 with Mc12-CD80 cells grew progressively in all inoculated nu/nu mice; in a 1:1 mixture with parental Mc12 cells, Mc12-IL-2 cells were able to cause regressions in approximately 50% of nu/nu mice; the 1:1 mixture of Mc12-IL-2 and Mc12-CD80 transfectants showed only transient growth and regressed during four weeks in all inoculated nu/nu mice. Adoptive transfer of cell-mediated immunity revealed that spleen cells from tumor regressors were capable of transferring the resistance to Mc12 tumor in nu/nu mice. The spleen cells from tumor regressors were not cytolytic when allowed to react in vitro with Mc12, Mc12-IL-2, or Mc12-CD80 target cells. However, when grown in IL-2-containing medium, splenocytes from tumor regressors, but not the splenocytes from tumor progressors, could develop cytolytic activity directed against Mc12 target cells that was comparable to that of the splenocytes from tumor-free controls. These results suggest that the rejection of tumors in nu/nu mice was mediated by IL-2-dependent mechanisms in which the CD80 molecule played a co-stimulatory role; the results also indicate that the ability to be activated by IL-2 and to give rise to cytolytic activity of nu/nu splenocytes from tumor progressors is decreased.
Keywords: Mice; Signal Transduction; myši inbrední C57BL; transplantace nádorů; antigeny CD80; myši; slezina; interleukin-2; transfekce; methylcholanthren; B7-1 Antigen; Immunity, Cellular; Neoplasm Transplantation; buněčná imunita; Carcinogens; experimentální sarkom; mužské pohlaví; karcinogeny; myši nahé; Male; Sarcoma, Experimental; imunoterapie adoptivní; Interleukin-2; Animals; zvířata; Transfection; signální transdukce; Methylcholanthrene; Mice, Inbred C57BL; Spleen; Immunotherapy, Adoptive; Mice, Nude